The CBIA Method in Community Empowerment: Promotional and Preventive Efforts for Hypertension in Klaten Regency Central Java - ramayani, septiana laksmi; Nur Rochma, Annisa; Agnesti, Faticha Yulia; Puspita, Apriliya Indah; Fujiana, Desi; Diana, Dhea Ayu First; Nurani, Liza Zahra; Sefiadita, Elvine Sefiadita (Jurnal Mitra Masyarakat (JMM), 2026)
Hypertension is an abnormal condition in blood flow, where systolic blood pressure increases to ≥140 mmHg and diastolic blood pressure to ≥90 mmHg. Hypertension is one of the non-communicable diseases that has become a global health issue due to its increasing prevalence and potential to cause various serious complications, such as heart disease, stroke, and kidney disorders. The low level of public knowledge regarding risk factors, prevention, and management of hypertension can lead to delays in disease detection and control. This community service activity aims to increase public knowledge about hypertension as a promotive and preventive effort thru the Active Learning Method (CBIA). The activity was conducted on January 20, 2026, in Ngerangan Village, Bayat District, Klaten Regency, Central Java, involving 30 PKK members as participants. The sequence of the community service activities includes blood pressure screening, hypertension exercise, pretest, counseling, interactive discussion, and posttest. Data analysis was conducted descriptively by comparing pretest and posttest results based on the percentage of correct answers calculated using Sugiyono's formula to determine the knowledge level categories of the participants. The results of the activities showed an increase in the average knowledge level of the participants from 91.3% in the pretest to 97.1% in the posttest. The percentage of participants with good knowledge categories increased from 90% (27 participants) to 96.7% (29 participants), while participants with poor knowledge categories, who previously numbered 2 (6.7%), were no longer found after the counseling. The results indicate that the CBIA method is effective in enhancing the community's understanding of hypertension. With the increased knowledge of the participants, it is hoped that the community will be able to adopt healthy lifestyle behaviors and actively participate in the prevention and control of hypertension within the family and community